Complement Inhibition in Severe COVID-19 Acute Respiratory Distress Syndrome - Raghunandan, Sharmila; Josephson, Cassandra D.; Verkerke, Hans; Linam, W. Matthew; Ingram, Treva C.; Zerra, Patricia E.; Arthur, Connie M.; Stowell, Sean R.; Briones, Michael; Chonat, Satheesh (Frontiers in Pediatrics, 2020)
Most children with COVID-19 have asymptomatic or mild illness. Those who become critically ill suffer from acute respiratory distress syndrome (ARDS) and acute kidney injury (AKI). The rapid deterioration of lung function has been linked to microangiopathic and immune-mediated processes seen in the lungs of adult patients with COVID-19. The role of complement-mediated acute lung injury is supported by animal models of SARS-CoV, evaluation of lung tissue in those who died from COVID-19 and response of COVID-19 ARDS to complement inhibition. We present a summary of a child with COVID-19 disease treated with convalescent plasma and eculizumab and provide a detailed evaluation of the inflammatory pathways.